The small mammals of Bario, Kelabit highlands Sarawak - Mohd Tajuddin, Abdullah; Mustafa, Abdul Rahman; Besar, Ketol (1999)
The aim of the study was to find the composition of the small mammals in the forests of Bario. Two study sites were chosen; the salt well near Pa' Ukat and the area down stream of the new reservoir near Kampong Arudalan. Rodents and bats were captured using live traps and mist nets respectively. A total of 42 animals was captured comprising of 7 species of small mammals, five were bats and two were rodents. The commonest mammal was Cynopterus brachyotis.